A comparison of outcomes in ultrasonography guided versus landmark guided corticosteroid injection for the treatment of adhesive capsulitis - K. M., Gopinath; G. Nair, Aishwarya; I., Suresh; Gowda, Suhas; Swaroop, Bysani; Kadiri, Venkatesh (International Journal of Research in Medical Sciences, 2023)
Background: Adhesive capsulitis is a debilitating disease in an otherwise healthy individual. Intra-articular corticosteroid injections offer a cost-effective, non-operative treatment option. However, it is currently unclear whether an ultrasound-guided injection relieves the symptoms of shoulder pain more effectively than if the injection was delivered landmark-guided. Methods: Eighty patients with adhesive capsulitis were randomized to two intervention groups - landmark guided and ultrasound (USG) guided. The functional status of the patients was documented prior to the intervention. Following allocation, the intra-articular steroid was administered either under USG guidance or following identification of the site of injection using landmarks. Follow-up was done on day 5, 3 weeks, 6 weeks, and 12 weeks post procedure to document the functional status. Results: The difference in visual analogue score (VAS) between the two arms was found to be statistically significant in favour of the ultrasound guided technique only on day 5 and day 21. On the other hand, the difference in disability of arm, shoulder, and hand (DASH) score between the 2 arms was found to be statistically significant in favour of the ultrasound guided technique on day 5, 21, 42 and 84. Finally, in our study, both shoulder flexion and abduction on day 84 achieved a statistically significant improvement, favouring the ultrasound guided arm. Conclusions: Ultrasound guided corticosteroid injections may offer modestly better short-term functional outcome and symptom relief when compared with landmark guided corticosteroids.